2013
DOI: 10.1186/1129-2377-14-25
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate modulates habituation in migraine: evidences from nociceptive responses elicited by laser evoked potentials

Abstract: BackgroundLack of habituation during repetitive stimulation is the most consistent interictal abnormality of cortical information processing observed in migraine. Preventive migraine treatments might act by stabilizing cortical excitability level and thus the habituation to external stimuli.MethodsWe examined the effects of preventive treatment with topiramate on migraineur’s habituation to nociceptive stimulation. Scalp potentials were evoked by Nd-YAP Laser stimulation of the hand dorsum and supraorbital reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 35 publications
2
41
2
Order By: Relevance
“…In another study we had found similar electrophysiological abnormalities in healthy volunteers with a familial history of migraine, although they did not have any headache themselves at the time of the recordings [37]. A recent publication found that topiramate [38], one of the most effective drugs in migraine prevention, was able to normalize habituation in these patients. At baseline, episodic migraineurs showed a significant lack of habituation, which disappeared after 2 months of treatment with topiramate, and the individual improvement of habituation was positively correlated with the clinical benefit.…”
Section: Discussionmentioning
confidence: 75%
“…In another study we had found similar electrophysiological abnormalities in healthy volunteers with a familial history of migraine, although they did not have any headache themselves at the time of the recordings [37]. A recent publication found that topiramate [38], one of the most effective drugs in migraine prevention, was able to normalize habituation in these patients. At baseline, episodic migraineurs showed a significant lack of habituation, which disappeared after 2 months of treatment with topiramate, and the individual improvement of habituation was positively correlated with the clinical benefit.…”
Section: Discussionmentioning
confidence: 75%
“…Animal studies demonstrated that antiepileptic drugs with proven effects on CM, could modulate nociceptive transmission and central sensitization phenomena [26]. Neurophysiological studies based on cortical re- sponses to nociceptive stimuli confirmed that topiramate as well as OBT-A could modulate reduced habituation to painful inputs, which may be the neurophysiological sign of central sensitization [7,27]. Unfortunately, the present patient group was not so numerous to permit the evaluation of the subgroups treated with amitriptyline and topiramate, who could ideally show a greater improvement of allodynia.…”
Section: Obt-a Has Effect On Allodyniamentioning
confidence: 95%
“…In episodic migraine the late component of laser evoked potentials (LEPs), mainly generated in the insular and anterior cingulate cortices, elicited by either cephalic (usually supraorbital) or extracephalic (usually hand dorsum) stimulation does not habituate during stimulus repetitions over short [65] or long durations [66-68]. Deficient habituation was also observed for the early N1 LEP component, mainly generated in the secondary somatosensory cortex [66,69]. In two studies performed in episodic migraine between attacks using contact-heat evoked potentials (CHEPS) and source localization with standardized LORETA (sLORETA) mapping it was shown that the lack of habituation to the noxious heat stimuli is probably related to the inability of the orbitofrontal cortex (OFC) to filter out correctly the pain information [70,71].…”
Section: Reviewmentioning
confidence: 99%